Preservation Cranioplasty vs. Structural Cranioplasty: A New Concept to Categorize the Treatment of Craniosynostosis - Matushita, Chaline Mari; Lee, Ho Hyung; Choi, Jong Woo (Archives of Plastic Surgery)
We propose a new categorization of craniosynostosis treatment: preservation cranioplasty, minimizing tissue disruption and enabling natural growth, and structural cranioplasty, involving extensive reshaping for severe deformities. Surgical choice depends on age, severity, and resources.